TRANSFORMASI PENDIDIKAN AGAMA ISLAM DI ACEH DARI PERIODE KLASIK HINGGA MODERN - Miswari, Miswari (LPPM Institut Nida El-Adabi, 2024)
This article aims to discuss the development of Islamic religious education in Aceh. This qualitative research uses literature review to collect data. The data obtained is analyzed, verified and presented. Research findings show that the early Islamic educational institutions in Aceh were a transformation of the Hindu era education system where the learning media did not experience significant changes. The first recorded Islamic educational institution in Aceh was Zawiyah Cot Kala in Aramiyah, Bayeun, East Aceh which was under the Peureulak Sultanate. Next Dayah Blang Pria in Samudra Pasai. Then Jami'ah Baiturrahman and Dayah Syiah Kuala during the Aceh Darussalam Sultanate. Entering the modern period, Islamic religious education is carried out by various Islamic organizations such as Madrasah Khairiyah by Tuanku Raja Keumala, Madrasah Sa'adah Abadiyah by Daud Beureueh and Abdullah Ujong Rimba, Madrasah Ahlussunnah Waljamaah by Sayyid Husain Syihab, Al-Islam College by Teungku Abdurrahman Seulimum, Jamiah Al-Muslim by Teungku Abdurrahman Meunasah Meucap, and the Normal Islamic Institute. After independence, there were several modern educational institutions such as Madrasah Ulumul Qur'an (MUQ) Langsa, Islamic Boarding School Darul Faqih Qur'ani, Islamic Boarding School Insyafuddin, Islamic Boarding School Jeumala Amal, and several other educational institutions. All these modern educational institutions mutually improve the quality of religious learning as well as general science learning.